Evaluation model of dry mixes for plas-terboards/Statybinių mišinių, naudotinų su gipskartonio plokštėmis, vertinimo modelis - Dėjus, Titas; Mitkus, Sigitas (Journal of Civil Engineering and Management, 2001)
Dry building mixtures’ market analysis demonstrated that construction arrangement experts sometimes do not have enough information or are not aware of the methods enabling them to choose effective dry building mixtures to be used while erecting partitions of plasterboards. Pre-project documentation usually does not specify, which of the mixtures (in most cases called ‘putty’) should be used in certain cases. That results in certain problems at the pre-construction stage as well as at the time of setting and puttying seams of the plasterboard partitions and at the time of preparing the partitions for final finish. There are even more alternatives to be considered while increasing processibility of erection of the whole partition: the same type of putty may be used for setting all layers in order to facilitate the suppliers’ work, or firmer putty may be used for the first layers and a different one – for the final layer in order to achieve better quality; setting a seam which is particularly resistant to cracks or confining oneself on a weaker seam, which will be later covered by wall-paper or ceramic tiles, etc. Abundance of alternatives and possibility to put into practice any of them creates quite a great emotional tension. In this case subjective opinion of an employee making the decision becomes determinant. Which of the subjective factors of evaluation are the most important? Questioning of some building-related employees was carried out in order to answer the question. 59 respondents have filled in the questionnaire. Table 4 provides the results of the respondents’ determination on the most important factors of putty evaluation and choice. Methods of determining the importance of effectiveness factors are described in detail in certain literature [4, 5, 6, 7]. This article suggests evaluation of the product’s usefulness subject to the formula (2) with certain restrictions or following the SAW method (3). The ideal point method (4)–(9) specified in this evaluation model should be used only if special software is available. Article in Lithuanian. First Published Online: 30 Jul 2012